(untitled) (Jóvenes en la Ciencia, 2024)
During their academic career, the students of the Bachelor’s Degree in Nursing and Midwifery at the Irapuato-Salamanca campus have faced a series of obstacles in order to overcome and achieve their goals. However, throughout this course of study and effort, they are faced with situations or factors that influence their quality of sleep, affecting academic performance and triggering complications that can affect their health. Objective: To analyze the factors that influence the quality of sleep in students of the University of Guanajuato of the degree in Nursing and Obstetrics Campus Irapuato-Salamanca. A research was carried out with an analytical, transversal, retrospective, observational and quantitative, non-experimental approach, with a sample of 100 respondents at convenience, corresponding to students from different semesters (2nd to 8th) to whom it was applied. the Pittsburgh Sleep Quality Index questionnaire being carried out in a single application for data collection at different educational grades. It was shown that 12% of the students have good quality of sleep and 88% have poor quality. The main factors that lead to poor quality sleep are: headache, homework, worry, school stress, sleep paralysis, work, environmental noises, hunger, anxiety and insomnia. It was demonstrated that students of the Bachelor of Nursing and Midwifery (2nd to 8th semester) have poor sleep quality as a result of not sleeping the recommended number of hours.